ENVIRONMENTAL MANAGEMENT ACCOUNTING AND GOOD CORPORATE GOVERNANCE MECHANISMS ON ENVIRONMENTAL PERFORMANCE - Lestari, Rini; Faturrahman, Muhammad Akbar (UPT Publikasi Ilmiah UNISBA, 2024)
This study aims to examine the effect of environmental management accounting and good corporate governance mechanisms on the environmental performance of manufacturing companies. The measurement of environmental management accounting used in this study uses content analysis, while the measurement of GCG uses 4 sub-variables, namely independent board of commissioners, managerial ownership, institutional ownership, and audit committee. Furthermore, the measurement of environmental performance refers to the PROPER score. The research method used is verification with a quantitative approach, using purposive sampling and producing a total sample of 32 manufacturing companies spread across Indonesia. The results of this study indicate that the application of environmental management accounting and the audit committee has an influence on environmental performance, while the independent board of commissioners, managerial ownership, and institutional ownership have no effect on environmental performance. Keywords : Environmental Management Accounting, Good Corporate Governance Mechanisms, Manufacturing Companies, PROPER.